2020
DOI: 10.3892/ijo.2020.5031
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic inhibitors eliminate senescent melanoma BRAFV600E cells that survive long‑term BRAF inhibition

Abstract: It is estimated that ~50% of patients with melanoma harbour B-Raf (BRAF)V600 driver mutations, with the most common of these being BRAFV600E, which leads to the activation of mitogen-activated protein kinase proliferative and survival pathways. BRAF inhibitors are used extensively to treat BRAF-mutated metastatic melanoma; however, acquired resistance occurs in the majority of patients. The effects of long-term treatment with PLX4032 (BRAFV600 inhibitor) were studied in vitro on sensitive V600E BRAF-mutated me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 59 publications
(60 reference statements)
1
11
0
Order By: Relevance
“…Concerning BRAF-mutant melanoma, many studies have pointed out the role of epigenetic mechanisms, mainly through HDAC, in resistance to BRAF and MEK inhibition [ 158 , 159 ], suggesting also the possibility of preventing the onset of resistance by using HDACi [ 160 ]. Indeed, an ongoing trial is investigating the HDACi vorinostat in resistant BRAF V600-mutant advanced melanoma patients (NCT02836548).…”
Section: From the Past To The Future Of Braf-mutant Melanoma Treatmentioning
confidence: 99%
“…Concerning BRAF-mutant melanoma, many studies have pointed out the role of epigenetic mechanisms, mainly through HDAC, in resistance to BRAF and MEK inhibition [ 158 , 159 ], suggesting also the possibility of preventing the onset of resistance by using HDACi [ 160 ]. Indeed, an ongoing trial is investigating the HDACi vorinostat in resistant BRAF V600-mutant advanced melanoma patients (NCT02836548).…”
Section: From the Past To The Future Of Braf-mutant Melanoma Treatmentioning
confidence: 99%
“…Treatment with the HDAC inhibitor vorinostat depleted MAPK inhibitor-resistant cells by increasing reactive oxygen species, increasing drug-sensitive clones that succumbed to BRAFi [ 113 ]. Another study showed that long-term treatment with the BRAFi PXL4032 on sensitive BRAF mutant melanoma cell lines induced senescent resistant clones that portrayed a stem cell-like phenotype and had an aberrant expression of multiple epigenetic modifiers such as HDAC6 [ 114 ]. This senescent state was reversed by HDAC inhibitors such as SAHA and mocetinostat (MGCD0103) [ 114 ].…”
Section: Epigenetic Modifiers As Therapeutic Adjuvants For Melanoma Patientsmentioning
confidence: 99%
“…Another study showed that long-term treatment with the BRAFi PXL4032 on sensitive BRAF mutant melanoma cell lines induced senescent resistant clones that portrayed a stem cell-like phenotype and had an aberrant expression of multiple epigenetic modifiers such as HDAC6 [ 114 ]. This senescent state was reversed by HDAC inhibitors such as SAHA and mocetinostat (MGCD0103) [ 114 ].…”
Section: Epigenetic Modifiers As Therapeutic Adjuvants For Melanoma Patientsmentioning
confidence: 99%
“…Increasing evidence has been reported for the synergistic and additive effects of the joint use of HDAC inhibitors and BRAF inhibitors in colon cancer and melanoma (Lai et al, 2013;Carson et al, 2015;Fu et al, 2019). The combination of PLX4032 and HDAC inhibitors have been displayed complete elimination of cancer cells, and to reduce the progress of resistance to BRAF inhibitors (Madorsky Rowdo et al, 2020). Recently, Emmons et al revealed that HDAC8 inhibitors could enhance the durability of BRAF inhibitor therapy (Mer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%